Inclusion of a connected adaptive resistance exercise machine in a 6-week training regimen with collegiate basketball players - Yamamoto, T.; Pandit, B.; Viggiano, M.; McCabe, C.; Mickelsen, E.; Geralds, C.; Jeon, M.; Ulitsky, I.; Kim, A.; Mologne, M. S.; Dolezal, B. A. (Scientific Journal of Sport and Performance, 2023)
In this study, we aimed to determine the effects of incorporating connected adaptive resistance exercise (CARE) into a training regimen with collegiate basketball players on lower body performance metrics. Thirty-two male participants (aged 18-26) with collegiate basketball experience trained thrice weekly for 6 weeks with a periodized training program that included CARE and were randomized 1:1 and blinded to an intervention group (n = 16; where the CARE used accentuated eccentric loading (AEL)) or an active control group (n = 16; where the CARE did not use accentuated eccentric loading (ACTL)). Standard anthropomorphic measures along with one repetition maximum (1-RM) back squat, vertical jump height, and peak power were assessed prior to and following completion of the training regimen. Both groups demonstrated significant increases in 1-RM back squat, jump height, and peak power (both p < .001). However, AEL yielded significantly greater improvements compared to ACTL across these measures (p <.001, g = 0.91; p <.001, g = 0.89; p <.001, g = 0.92, respectively). The findings of the present study demonstrate that the inclusion of CARE may be a superior strategy for improving performance variables of lower-body strength, peak power and jump height for male collegiate basketball players.